Computer-assisted dieting: effects of a randomised controlled intervention. - Schroder KEE (Psychology & Health, 2010)
In this pilot study, the effects of two computer-assisted dieting (CAD) interventions on weight loss and blood chemistry were examined among overweight and obese adults. Participants (91 community members, average age 42.6 years) were randomly assigned to CAD-only (a single-session introduction and provision of a dieting software, n = 30), CAD plus an additional four-session self-management group training (CAD+G, n = 31) and a waitlist control group whose members were randomised into the two interventions at the 3-month follow-up (n = 30). A three (group)-by-two (time) repeated measures ANOVA revealed no significant group by time interaction during the initial 3-month period. However, the two intervention groups combined showed a significant, though moderate weight loss relative to the control group. Further, although a general improvement was found with regard to the lipid panel results during the first 3 months of the trial, the treatment by time interaction was not significant. A comparison of the developments in the two intervention groups during the 3- to 6-month follow-up time period revealed a tendency towards greater weight regain in the CAD-only condition. The evidence suggests that CAD supports initial weight loss; however, additional self-management training might be necessary to support maintenance.